Gwendy's button box [compact disc, unabridged] - King, Stephen, 1947- (Simon & Schuster Audio, 2017)
There are three ways up to Castle View from the town of Castle Rock: Route 117, Pleasant Road, and the Suicide Stairs. Every day in the summer of 1974, twelve-year-old Gwendy Peterson has taken the stairs, which are held by strong, if time-rusted, iron bolts and zig-zag up the cliffside. Then one day when Gwendy gets to the top of Castle View, after catching her breath and hearing the shouts of kids on the playground below, a stranger calls to her. There on a bench in the shade sits a man in black jeans, a black coat, and a white shirt unbuttoned at the top. On his head is a small, neat black hat. The time will come when Gwendy has nightmares about that hat.